2022
DOI: 10.1088/1361-6382/acad60
|View full text |Cite
|
Sign up to set email alerts
|

Relativity of superluminal observers in 1 + 3 spacetime

Abstract: We develop an extension of special relativity in 1+3 dimensional spacetime to account for superluminal inertial observers and show that such an extension rules out the conventional dynamics of mechanical point-like particles and forces one to use field-theoretic framework. Therefore we show that field theory can be viewed as a direct consequence of extended special relativity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…, which therefore indicates the possibility of superluminal light propagation [27]. This orthogonal property has now been observed in near field electromagnetic radiation [22,23,28], but we would also predict that this radiation will be superluminal, based on equation (34).…”
Section: General Null Particlesmentioning
confidence: 51%
“…, which therefore indicates the possibility of superluminal light propagation [27]. This orthogonal property has now been observed in near field electromagnetic radiation [22,23,28], but we would also predict that this radiation will be superluminal, based on equation (34).…”
Section: General Null Particlesmentioning
confidence: 51%
“…It is worth noting that we have recently demonstrated that a covariant quantum field theory of tachyons with a positive-definite spectrum and a stable, invariant vacuum can be constructed [7]. In this study, as well as in our previous work [8], we emphasize that the Higgs mechanism incorporates tachyonic fields. As a result, our ongoing research opens the way to study fully quantized theory of spontaneous symmetry breaking.…”
mentioning
confidence: 53%
“…One of the reasons for the interest in tachyons was the overwhelming success Salam-Weinberg model (see for instance [13,[17][18][19]) where the gauge symmetry is spontaneously broken by filling the vacuum with Higgs field particles which can be considered formally as tachyons which have been converted into subluminal particles. It is very intriguing, that even though Einstein's ban on faster-than-light speeds does not prohibit the existence of superluminal particles (tachyons) so far still there are no convincing experiments for the existence of such exotic particles [20].…”
Section: Introductionmentioning
confidence: 99%